Influential factors for adhesion to the vaccine against human papillomavirus: an integrative review (Research, Society and Development, 2022)
Objective: To analyze the factors influencing adherence to the Human Papillomavirus vaccine in schoolchildren. Methodology: Integrative Literature Review (RIL) took place from February to April 2018. The integrative review was carried out at the Virtual Health Library (VHL), which includes the Latin American and Caribbean Literature on Health Sciences (LILACS), IBECS, Medical Literature Analysis and Retrieval System Online (MEDLINE), Cochrane Library and Scientific Electronic Library Online (SciELO). After reading and applying the criteria, 22 articles were selected for full analysis. Results: As for the factors influencing adherence to the HPV vaccine, these were divided into two groups: positive and negative factors. Within each group, the most discussed aspects in the studies were chosen, enabling them to be grouped for a better understanding, listed in three groups: knowledge, attitudes and perceptions of parents/guardians; Sociocultural factors and health education. Conclusion: The studies bring several influencers in the decision-making process, both positive and negative in relation to the acceptance of the vaccine. The factors described here are of great relevance, because through their knowledge, health professionals will be able to establish an active role in the development of strategies aimed at greater adherence to the vaccination campaign against the Human Papillomavirus (HPV).